A Review of Maite Correa’s Article on Forensic Linguistics: An Overview of the Intersection and Interaction of Language and Law - Afifuddin, Afifuddin (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2023)
This review article attempted to provide readers with a valuable, informative, and critical summary of a specific topic or area in the field of forensic linguistics. Maite Correa’s article entitled Forensic Linguistics: An Overview of the Intersection and Interaction of Language and Law is the subject of this study. The article presents a summary of the expansive field of forensic linguistics (FL) and shows the various ways in which the discipline might help to a criminal justice system. A synopsis of some of the most famous and widely discussed legal cases is provided, as well as an explanation of the intersections between applied linguistics and other academic fields. In a critical point of view, the author has thoroughly discussed each point of the debate. The problem of various types is mentioned and clearly analyzed. The problems were described first, followed by explanations to help readers understand the issues being discussed. Nevertheless, the article lacks compatibility, so readers might only get its explanation without knowing what kind of methodology was used to analyze the data.